1993
DOI: 10.1104/pp.101.2.545
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Sequencing of Radish Seed Calmodulin Antagonists Phosphorylated by Calcium-Dependent Protein Kinase

Abstract: A family of radish (Raphanus sativus) calmodulin antagonists (RCAs) was purified from seeds by extraction, centrifugation, batch-wise elution from carboxymethyl-cellulose, and high performance liquid chromatography (HPLC) on an SP5PW cationexchange column. l h i s RCA fraction was further resolved into three calmodulin antagonist polypeptides (RCA1, RCAZ, and RCA3) by denaturation i n the presence of guanidinium HCI and mercaptoethanol and subsequent reverse-phase HPLC on a Ca column eluted with an acetonitril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…With respect to the possible function of CaM in seeds during germination, it is interesting that recently a number of small proteins purified from radish seeds were identified as potent CaM antagonists (Polya et al, 1993). Moreover, a significant decrease in these antagonists and a simultaneous increase in CaM levels were observed during early phases of germination, implying that CaM-regulated processes are activated (Cocucci and Negrini, 1988).…”
Section: Gad Expression During Germinationmentioning
confidence: 99%
“…With respect to the possible function of CaM in seeds during germination, it is interesting that recently a number of small proteins purified from radish seeds were identified as potent CaM antagonists (Polya et al, 1993). Moreover, a significant decrease in these antagonists and a simultaneous increase in CaM levels were observed during early phases of germination, implying that CaM-regulated processes are activated (Cocucci and Negrini, 1988).…”
Section: Gad Expression During Germinationmentioning
confidence: 99%
“…It has been shown that napin has a calmodulin antagonist activity and it has the potential calmodulininteracting structural elements (Polya et al 1993;Neumann et al 1996b, c). Oxidised napin complexes can be effective proteinase inhibitors and it was suggested that this might contribute to the biological activity of this protein as an anti-fungal agent (Neumann et al 1996a, b;Polya 1997).…”
Section: Resultsmentioning
confidence: 96%
“…24,25 In vitro bioactivities, like enzyme inhibition and antifungal activity of 2S albumins, have been reported, but the in vivo significance of these activities is unknown. 26,27 2S albumins have been shown to represent allergens, for example, in sunflower seed, white mustard, oriental mustard, sesame seed, brazil nut, and castor bean. 19,20,[28][29][30][31] At the moment, the route of sensitization of oilseed rape or turnip rape allergy is unclear.…”
Section: Discussionmentioning
confidence: 99%